A case of clinical worsening after stereo-electroencephalographic-guided radiofrequency thermocoagulation in a patient with polymicrogyria - Lorenzo Ferri; Roberto Mai; Lidia di Vito; Veronica Menghi; Matteo Martinoni; Piergiorgio D'Orio; Laura Licchetta; Lorenzo Muccioli; Carlotta Stipa; Paolo Tinuper; Francesca Bisulli (Epilepsy & Behavior Reports, 2023)
Radiofrequency thermocoagulation (RF-TC) is a wide-used procedure for drug-resistant epilepsy. The technique is considered safe with an overall risk of 1.1% of permanent complications, mainly focal neurological deficits. We report the case of a patient with drug-resistant epilepsy who complained of immediate seizure worsening and an unexpected event seven months following RF-TC.A 35-year-old male with drug-resistant epilepsy from the age of 18 years underwent stereoelectroencephalography (SEEG) implantation for a right peri-silvian polymicrogyria. He was excluded from surgery due to extent of the epileptogenic zone and the risk of visual field deficits. RF-TC was attempted to ablate the most epileptogenic zone identified by SEEG. After RF-TC, the patient reported an increase in seizure severity/frequency and experienced episodes of postictal psychosis. Off-label cannabidiol treatment led to improved seizure control and resolution of postictal psychosis.Patients with polymicrogyria (PwP) may present with a disruption of normal anatomy and the co-existence between epileptogenic zone and eloquent cortex within the malformation.RF-TC should be considered in PwP when they are excluded from surgery for prognostic and palliative purposes. However, given the complex interplay between pathological and electrophysiological networks in these patients, the remote possibility of clinical exacerbation after RF-TC should also be taken into account.